The relationship between hamstring injury risk screening tests and lower limb biomechanics during sprint - Ting, L.; Hanjun, L. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to explore the relationship between hamstring injury risk screening test scores and lower limb biomechanical characteristics during sprint, and to select more appropriate screening tests from the perspective of biomechanics. Soccer players(n=18) experienced three kinds of hamstring injury screening tests(Nordic hamstring test, ultrasound test, straight-leg-raising test) and collected kinematics data and dynamics data of the lower extremities during sprint. The result of the Nordic Hamstring Test was significantly positively correlated with the peak force of semimembranosus muscle, semitendinosus muscle and biceps femoris long head during sprint (P<0.05), and the correlation coefficients were 0.504, 0.506 and 0.429, respectively. It was significantly negatively correlated with thepeakstrain (P<0.05), and the correlation coefficients were -0.462, -0.460 and -0.385, respectively.There was no significant correlation among other data. The Nordichamstring test is the mostsuitable for the risk screening of hamstring injury.Ultrasoundtestmayhasa certain screening effect, but it is difficult to operate and spread. The straight-leg-raising test is not recommended for continued use.